1999
DOI: 10.1046/j.1365-3091.1999.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

The Saharan debris flow: an insight into the mechanics of long runout submarine debris flows

Abstract: New 3·5 kHz profiles and a series of piston cores from the north‐west African margin provide evidence that the Saharan debris flow travelled for more than 400 km on a highly fluid, low‐friction layer of poorly sorted sediment. Data suggest that the Saharan debris flow is a two‐phase event, consisting of a basal, volcaniclastic debris flow phase overlain by a pelagic debris flow phase. Both phases were emplaced on the lower continental rise by a single large debris flow at around 60 ka. The volcaniclastic flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(154 citation statements)
references
References 33 publications
4
147
1
2
Order By: Relevance
“…This latter constraint is justi¢ed by reference to small-scale £ume experiments and may not hold for all submarine debris £ows. For example, Gee et al (1999) document signi¢cant proximal erosion by the extensive Saharan debris £ow o¡shore from West Africa. Deposition by debris £ows within Pratson et al's model can create a depression at the slope break.…”
Section: Discussionmentioning
confidence: 99%
“…This latter constraint is justi¢ed by reference to small-scale £ume experiments and may not hold for all submarine debris £ows. For example, Gee et al (1999) document signi¢cant proximal erosion by the extensive Saharan debris £ow o¡shore from West Africa. Deposition by debris £ows within Pratson et al's model can create a depression at the slope break.…”
Section: Discussionmentioning
confidence: 99%
“…1B), que parece pertenecer a un edificio volcánico más antiguo, al igual que el monte submarino Henry, situado al SE, ambos cubiertos por varios metros de sedimentos (Mitchell, 1993). En campañas oceanográficas en zonas próximas (<3 km de distancia) a la localización de la actual erupción de 2011-12, se dragaron numerosas muestras de lavas (picritas y basaltos alcalinos) e hialoclastitas con escaso grado de alteración, lo que evidencian una edad muy reciente (Mitchell, 1993;Urgeles et al, 1997Urgeles et al, , 1998Schmincke et al, 1998;Gee et al, 1999;Ye et al, 1999;Schmincke & Graf, 2000;Krastel & Schmincke, 2002;Masson et al, 2002).…”
Section: El Rift S De El Hierrounclassified
“…Elverhbi et al, 1997;Laberg and Vorren, 2000;Nygård et al, 2002). Debris flows can even occur on slopes with gradients as low as 0.058 (Schwab et al, 1996;Gee et al, 1999), but the suggested flow mechanisms on such gentle slopes require very special pre-conditions, such as loading and mobilization of basal volcaniclastic sands.…”
Section: Structure Facies Typementioning
confidence: 99%